Agglomeration of nano- and microplastic particles in seawater by autochthonous and de novo-produced sources of exopolymeric substances - Summers, Stephen (2019)
Microplastics (<5 mm) have often been studied under in-vitro conditions where plastics have been investigated in isolation. However, in the natural environment microplastics readily form agglomerates conferring the particles with properties different to their pristine counterparts. Here, we examined the interaction of exopolymers with polystyrene nanoplastics and microplastics. Formation of plastic agglomerates was examined using simulated sea surface conditions. Flow cytometry coupled with microscopy revealed that nano- and microplastic particle spheres form agglomerates in seawater with a mucilagenous material and an associated microbial community. To characterise this material, differential staining methods revealed it to be glycoprotein in composition. Exposing increasing concentrations of a marine bacterial glycoprotein EPS to nano- or microplastics revealed that these types of polymers contribute to the formation and abundance of plastic agglomerates. This work highlights the importance of EPS on the fate of plastic and future research should take this into account when evaluating the impact of plastics.